Evaluating the gender wage gap in Georgia, 2004 - 2011 - Tamar Khitarishvili (Levy Economics Institute of Bard College, 2013)
This paper evaluates the gender wage gap among wage workers along the wage distribution in Georgia between 2004 and 2011, based on the recentered influence function (RIF) decomposition approach developed in Firpo, Fortin, and Lemieux (2009). We find that the gender wage gap decreases along the wage distribution, from 0.64 log points to 0.54 log points. Endowment differences explain between 22 percent and 61 percent of the observed gender wage gap, with the explained proportion declining as we move to the top of the distribution. The primary contributors are the differences in the work hours, industrial composition, and employment in the state sector. A substantial portion of the gap, however, remains unexplained, and can be attributed to the differences in returns, especially in the industrial premia. The gender wage gap consistently declined between 2004 and 2011. However, the gap remains large, with women earning 45 percent less than men in 2011. The reduction in the gender wage gap between 2004 and 2007, and the switch from a glass-ceiling shape for the gender gap distribution to a sticky-floor shape, was driven by the rising returns in the state sector for men at the bottom, and by women at the top of the wage distribution. Between 2009 and 2011, the decline in the gender wage gap can be explained by the decrease in men's working hours, which was larger than the decrease in women's working hours. We assess the robustness of our findings using the statistical matching decomposition method developed in \~Nopo (2008) in order to address the possibility that the high degree of industrial segregation may bias our results. The \~Nopo decomposition results enrich our understanding of the factors that underlie the gender wage gap but do not alter our key findings, and in fact support their robustness.
Keywords: J16; J31; P2; 330; Gender Wage Gap; Decomposition Methods; Wage Distribution; Transition Economies; Georgia; Glass Ceiling Effect; Sticky Floor Effect